Authigenic 10Be/9Be ratio signatures of the cosmogenic nuclide production linked to geomagnetic dipole moment variation since the Brunhes/Matuyama boundary. Issue 11 (14th November 2016) - Simon, Quentin; Thouveny, Nicolas; Bourlès, Didier L.; Valet, Jean‐Pierre; Bassinot, Franck; Ménabréaz, Lucie; Guillou, Valéry; Choy, Sandrine; Beaufort, Luc
Abstract: Geomagnetic dipole moment variations associated with polarity reversals and excursions are expressed by large changes of the cosmogenic nuclide beryllium‐10 ( 10 Be) production rates. Authigenic 10 Be/ 9 Be ratios (proxy of atmospheric 10 Be production) from oceanic cores therefore complete the classical information derived from relative paleointensity (RPI) records. This study presents new authigenic 10 Be/ 9 Be ratio results obtained from cores MD05‐2920 and MD05‐2930 collected in the west equatorial Pacific Ocean. Be ratios from cores MD05‐2920, MD05‐2930 and MD90‐0961 have been stacked and averaged. Variations of the authigenic 10 Be/ 9 Be ratio are analyzed and compared with the geomagnetic dipole low series reported from global RPI stacks. The largest 10 Be overproduction episodes are related to dipole field collapses (below a threshold of 2 × 10 22 Am 2 ) associated with the Brunhes/Matuyama reversal, the Laschamp (41 ka) excursion, and the Iceland Basin event (190 ka). Other significant 10 Be production peaks are correlated to geomagnetic excursions reported in literature. The record was then calibrated by using absolute dipole moment values drawn from the Geomagia and Pint paleointensity value databases. The 10 Be‐derived geomagnetic dipole moment record, independent from sedimentary paleomagnetic data, covers the Brunhes‐Matuyama transition and the whole Brunhes Chron. It provides new and complementary data on the amplitude and timing of millennial‐scale geomagnetic dipole moment variations and particularly on dipole moment collapses triggering polarity instabilities. Key Points: Authigenic 10 Be/ 9 Be ratios from three equatorial ocean cores are stacked and averaged outlining atmospheric 10 Be production changes The 10 Be cosmogenic nuclide overproduction episodes are systematically associated with geomagnetic dipole lows over the last 850 ka The 10 Be signatures of the Brunhes/Matuyama transition and Brunhes geomagnetic excursions yield distinct rates and durations